RUNTUHNYA JEMBATAN KUTAI KARTANEGARA DI TINJAU DARI ASPEK HUKUM PIDANA - Juma Raya (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTDiscussion of this issue is an interest of the author because of these events appeared several speculations about the case of the collapse of the bridge Kutai, the author would like to delve further into the elements of negligence and intentional done by workers and those responsible in the process of care and maintenance so that it can be seen how the chronology of these events in detail, therefore the authors raised the title of the collapse of the bridge in Kutai as Review Of Criminal Legal Aspects. The method of this thesis include the type of research that the method of juridical empirical, perimer and secondary data sources, research sites in the District Court Tenggarong Kutai regency, data collection techniques such as literature studies and studies in the field that includes observation, interviews, and documentation.The purpose of this study was to find out who is responsible and reviewing the consideration of judges in a verdict for the defendant cases Kutai bridge collapse and increase scientific treasures for the entire academic community of the University of August 17, 1945 samarinda.The results showed that one of the people responsible for the bridge collapse incident aquatic mammal is MUHAMMAD SYAHRIAR Fakhrurrozi, ST bin NOOR HADI, as Project Manager Kutai Bridge Maintenance Activities In 2011, consideration sentencing judge is to consider the second charge of Public Prosecutions is to commit criminal and punishable as provided in Article 360 paragraph (2) of the Criminal Code Jo. Article 55 paragraph (1) of the Criminal Code to-1,whose elements are as follows:a.Whoever elementb. Element for mistakesc. Elements lead others injuredd. Elements do, who told to do or participating in the act. The author hopes of events bridge collapse incident aquatic mammal is the Government and the company that holds a tender for more mature planning to the implementation of bridge maintenance in these events, in order to avoid further accidents resulting in loss of life of others.